FEM study to verify the effect of embossing and wave shapes on formability of stamping process for multi-hole etching metal foil using SUS316L material. - Toan, Nguyen Duc (Asean Engineering Journal)
In current study, to predict ductile fracture and spring back in making embossing shape using multi-hole etching metal foil of SUS316L material, FEM simulation was adopted. Ductile fracture criterion of forming limit diagram (FLD) and stress-strain curve based on experimental data were first input to ABAQUS/Explicit finite element code to predict failure and spring-back occurrences. Several simulations were then performed with the dimension changing of etching holes in order to simulate and investigate press formability of final product after forming process. The better case was obtained by utilizing simulation results. FEM simulation results were finally confirmed by the corresponding experiment. The FEM predictions were in good agreement with experimental result.